TRAF2 as a key candidate gene in clinical hepatitis B-associated liver fibrosis - Wu, Cichun; Zhang, Jian; Wang, Huiwen; Zhang, Wei; Liu, Jingqing; Zhou, Nianqi; Chen, Keyu; Wang, Ying; Peng, Shifang; Fu, Lei (Frontiers in Molecular Biosciences, 2023)
Objectives: Approximately 240 million individuals are infected with chronic hepatitis B virus (HBV) worldwide. HBV infection can develop into liver fibrosis. The mechanism of HBV-related liver fibrosis has not been fully understood, and there are few effective treatment options. The goal of this study was to use transcriptomics in conjunction with experimental validation to identify new targets to treat HBV-related liver fibrosis. Methods: To identify differentially expressed genes (DEGs), five liver tissues were collected from both healthy individuals and patients with chronic hepatitis B. NovoMagic and Java GSEA were used to screen DEGs and key genes, respectively. Immunocell infiltration analysis of RNA-seq data was, and the results were confirmed by western blotting (WB), real-time quantitative polymerase chain reaction (RT-qPCR), and immunohistochemistry. Results: We evaluated 1105 genes with differential expression, and 462 and 643 genes showed down- and upregulation, respectively. The essential genes, such as tumor necrosis factor (TNF) receptor-associated factor-2 (TRAF2), were screened out of DEGs. TRAF2 expression was abnormally high in hepatic fibrosis in patients with hepatitis B compared with healthy controls. The degree of hepatic fibrosis and serum levels of glutamate transaminase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL) were positively linked with TRAF2 expression. TRAF2 may be crucial in controlling T lymphocyte-mediated liver fibrosis. Conclusions: Our findings imply that TRAF2 is essential for HBV-induced liver fibrosis progression, and it may potentially be a promising target for the treatment of hepatic fibrosis in hepatitis B.